Solitary Median Maxillary Central Incisor Syndrome: An Exploration of the Pathogenic Mechanism - Li, Jie; Liu, Dandan; Liu, Yang; Zhang, Chenying; Zheng, Shuguo (Frontiers in Genetics, 2022)
This study aimed to identify the genetic cause of one Chinese family with solitary median maxillary central incisor (SMMCI) and explore the relationship between genotype and its phenotype. One Chinese family with clinical diagnosis of SMMCI was collected. Single Nucleotide Polymorphism (SNP) array was performed and identified variation was confirmed by whole-genome sequencing (WGS). The reported chromosomal abnormalities and pathogenic genes in patients with SMMCI in literature were reviewed and summarized. The proband was an 8-year-old boy presenting a typical solitary median maxillary central incisor with a range of other phenotypic anomalies, including ptosis. SNP array revealed a 14.3 Mbp heterozygous deletion at chromosome 18p11.32-p11.21 in the proband but not in the unaffected parents. WGS further confirmed the identified deletion. 194 genes were involved in the chromosome region. Among them, 12 genes had been shown to be associated with diseases, including TGIF1, a reported SMMCI gene. The de novo 18p deletion resulted in SMMCI in the present study. Our results provide new genetic evidence that structural abnormality in chromosome 18p contributes to solitary median maxillary central incisor.